Living sexuality stories of LGBTQ relationships, identities, and desires - Berry, Keith; Gillotti, Catherine M.; Adams, Tony E. (Brill Sense, 2019)
There has never been a more crucial time for an intimate and thorough examination of the ways in which sexuality informs people's lives. In 'Living Sexuality: Stories of LGBTQ Relationships, Identities, and Desires', the authors use autoethnography and personal narrative to provide first-hand accounts of the connections between sexuality, particularly LGBTQ identities, and the everyday experiences of relationships. Each story also invites readers to understand how sexuality informs communication as it occurs within diverse cultural contexts. In addition, the stories often focus on taboo issues overlooked or ignored in mainstream research about sexuality. Discussion questions appear at the end of each story that should stimulate engagement by students, instructors, and researchers.
Keywords: LGBT; Sexualverhalten; Sexual minorities / Social conditions; Sexual minorities / Identity; Sexual minorities / Sexual behavior; Aufsatzsammlung